Annual reporting practices: human capital information by Malaysian services companies - Noradiva Hamzah,; Mohamat Sabri Hassan,; Zakiah Muhammaddun Mohamed,; Azlina Ahmad,; Shukriah Saad, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The importance of human capital reporting has increased in recent years. Stakeholders such as financial analysts and investors are calling for more transparency and fuelling interest in the value that employees bring into a company. To date, annual reports rarely provide quantitative data on human capital; the information provided is often general and of little value. This study examines the human capital disclosure practices of listed services companies in Malaysia. The study uses a qualitative approach of content analysis to analyze disclosure in the 2009 annual reports of companies. The findings reveal that human capital disclosure varies across industries. This study indicates that majority of firms (in trading and services, finance, and hotel industries) generally provide more information on the related attribute of “employees”. Among the three industries, the finance industry provides the highest frequency. However, firms in the technology industry disclose more information on attributes related to “training and development”. These findings indicate that the nature of work expectation leads to variance of disclosure on human capital attributes (HCA) among firms within the services industries. Technology firms disclose more information on training and development to indicate that these attributes will help their employees stay updated with new developments in the technology industry. This study also indicates that there is inconsistency in disclosing HCA among firms in the services industry. Firms in the finance, technology, and hotel industries disclose more information on “facilities and benefits provided” whereas firms in the trading and services industry disclose more on attributes related to “effort for human capital development”.